2022
DOI: 10.3390/nu14193985
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Anti-Inflammatory Diet in Modulating Gut Microbiota and Controlling Obesity

Abstract: Obesity has consistently been associated with an increased risk of metabolic abnormalities such as diabetes, hyperlipidemia, and cardiovascular diseases, as well as the development of several types of cancer. In recent decades, unfortunately, the rate of overweight/obesity has increased significantly among adults and children. A growing body of evidence shows that there is a relationship between metabolic disorders such as obesity and the composition of the gut microbiota. Additionally, inflammation is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 143 publications
0
29
0
Order By: Relevance
“…The study by Dengo et al has shown that reduced body mass during four months in overweight and obese patients significantly improves aortic and carotid stiffness [ 17 ]. Thus, dietary interventions leading to body mass reduction are required to decrease arterial stiffness significantly by improving neuromodulation and blood pressure control [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Dengo et al has shown that reduced body mass during four months in overweight and obese patients significantly improves aortic and carotid stiffness [ 17 ]. Thus, dietary interventions leading to body mass reduction are required to decrease arterial stiffness significantly by improving neuromodulation and blood pressure control [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This diet also has an influence on gut microbiota leading to beneficial effects on obesity prevention. 53 The results of this study can help to better understand the effects of Ramadan fasting as a lifestyle modification on atherosclerosis indicators in people with metabolic syndrome. The results of this study and previous studies 23,24 (with the improvement of cardiovascular risk factors after Ramadan fasting) can help patients and clinicians evaluate Ramadan fasting's benefits and drawbacks to make decisions about it.…”
Section: Discussionmentioning
confidence: 90%
“…A less healthy diet (high fat and/or protein and low carbohydrates) is often characterized by less favourable ratio between the two dominating phyla: Bacteroides to Firmicutes [39]. For example, following a Mediterranean diet, that includes high intakes of plant foods, unsaturated vegetable oils, dairy products, and low amounts of meat, which in turn leads to lower protein intake compared to a Western diet, has been inversely associated with not only the risk of overweight and obesity but also increased abundance of health-related bacterial species and short-chain fatty acids (SCFA) producing bacteria [40]. Te human gut microbiota may play an important role in the development of obesity later in life but the exact mechanism by which the gut microbiota contribute to obesity is not well known and need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%